C-Myc-activated long non-coding RNA PVT1 enhances the proliferation of cervical cancer cells by sponging miR-486-3p. (14th January 2020) - Wang, Chang; Zou, Hao; Chen, Aiping; Yang, Hongjuan; Yu, Xinping; Yu, Xiao; Wang, Yankui
Abstract: Cervical cancer is one of the most prevalent gynecological malignancies. Although the functions of long non-coding RNA (lncRNA) plasmacytoma variant translocation 1 (PVT1) and c-Myc in tumorigenesis have been acknowledged, the roles of c-Myc and lncRNA-PVT1 in the proliferation of cervical cancer are still unclear. Our study is designed to demonstrate the regulatory network involving c-Myc and lncRNA-PVT1 in cervical cancer. Quantitative real-time PCR and western blot assays were performed in our research to estimate the expression levels of RNA and proteins. CCK8 assays were applied to demonstrate the viability of HeLa and SiHa cells. Immunofluorescence assay was then used to investigate the co-localization of lncRNA-PVT1 and miR-486-3p. Binding of c-Myc to the promoter region of PVT1 was identified by ChIP-assay. Functionally, upregulation of lncRNA-PVT1 enhanced the proliferation and viability of cervical cancer cells. Mechanistically, lncRNA-PVT1 sponged miR-486-3p and released its repression of extracellular matrix protein 1. Besides, c-Myc functioned as an activator of lncRNA-PVT1 and upregulated its expression by binding to the promoter of PVT1 in cervical cancer cells. lncRNA-PVT1 was upregulated by c-Myc and thus enhanced the proliferation of cervical cancer cells by sponging miR-486-3p.